EFL FOR KIDS: BEST PRACTICES FOR EARLY LANGUAGE LEARNING: EFL FOR KIDS: BEST PRACTICES FOR EARLY LANGUAGE LEARNING - Egambergenova, Gulruxsor (Журнал иностранных языков и лингвистики, 2025)
In recent years, the demand for English language education has increased globally, and many countries have introduced English instruction at younger ages. Children, especially those between the ages of 3 and 8, have the ability to acquire a new language more naturally and effortlessly than adults. This is due to their brain plasticity, curiosity, and the lack of fear in using a new language.